2018
DOI: 10.1016/j.hrthm.2017.11.031
|View full text |Cite
|
Sign up to set email alerts
|

Endocardial infarct scar recognition by myocardial electrical impedance is not influenced by changes in cardiac activation sequence

Abstract: Endocardial catheter measurement of electrical impedance can identify infarct scar regions, and in contrast to voltage mapping, the impedance data are not affected by changes in cardiac activation sequence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 18 publications
2
30
0
Order By: Relevance
“…The catheter has previously been studied in explanted swine tissue, with LI measured at a range of distances to the endocardium, RF powers and durations. 15 In contrast to voltage mapping, changing activation wavefront did not affect impedance data. 9 In a further in vivo swine study, electrogram amplitude, GI and LI were measured in the blood pool and in myocardial tissue locations in the RA, RV, and LV under intracardiac echocardiography (ICE).…”
Section: Discussionmentioning
confidence: 94%
“…The catheter has previously been studied in explanted swine tissue, with LI measured at a range of distances to the endocardium, RF powers and durations. 15 In contrast to voltage mapping, changing activation wavefront did not affect impedance data. 9 In a further in vivo swine study, electrogram amplitude, GI and LI were measured in the blood pool and in myocardial tissue locations in the RA, RV, and LV under intracardiac echocardiography (ICE).…”
Section: Discussionmentioning
confidence: 94%
“…Patients who died during follow‐up had lower baseline values than survivors. This result may reflect a higher percentage of patients with the LV lead located in an ischemic zone since infarct scar showed lower electrical impedance than the normal myocardium 1,9 . Finally, lower signal amplitudes for both right and LV leads were found in patients with death and VA events.…”
Section: Discussionmentioning
confidence: 99%
“…This result may reflect a higher percentage of patients with the LV lead located in an ischemic zone since infarct scar showed lower electrical impedance than the normal myocardium. 1,9 Finally, lower signal amplitudes for both right and LV leads were found in patients with death and VA events. This is not surprising as cytopenia and fibrosis are associated with lower signals and more advanced heart disease.…”
Section: Predictors Of Death and Ventricular Arrhythmiasmentioning
confidence: 96%
See 1 more Smart Citation
“…In addition, mapping with multi‐electrode catheters yields more data points and better variability in the angle of incidence and in the relationship to the vector of propagation, thereby reducing the individual confounding effects of bipolar voltage amplitude measurements. Finally a recent paper has shown that endocardial catheter measurement of the electrical impedance can identify infarct scar regions and, in contrast to voltage mapping, the impedance data is not affected by changes in cardiac activation sequence.…”
Section: Localization In Sinus Rhythm Of Channels Defined By Fixed Anmentioning
confidence: 99%